Public Signs In Komodo National Park, Flores-NTT: A Linguistic Landscape Study - Jem, Yosefina Helenora; Beda, Raimundus; Utami, Ni Made Verayanti; Agnes M.D Rafael (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2023)
This article aims at investigating language/s used in public signs in Taman Nasional Komodo (TNK), Labuan Bajo, Flores-NTT. It was designed as a qualitative study as the data are pictures, words, and sentences found in the public signs in TNK. The data were collected by doing an observation where every single sign found in TNK was photographed by using a Vivo y17 camera. After collecting the data, the data were analyzed by the following steps: data reduction, data display and data verification and conclusion. The result mentions that public signs in TNK divided into two types; they are monolingual and bilingual signs. The monolingual signs confirm that the public signs in TNK just use one language either Indonesian or English. However, bilingual refers to the public signs in TNK using both Indonesian and English for the same public sign. There are nine types of signs applied in TNK public signs. They are signs of place name, place manager, place description, map, history, notice, warning, appeal, and esthetic. Also, the signs have served purposes related to conveying information, representing symbols, and aiding in education.